Wendy A. Wiseman and Burak Kesgin (eds.), "Lost Kingdom: Animal Death in the Anthropocene" - Silvern, Steven E. (Journal for the study of religion, nature and culture, 2025)
Wendy A. Wiseman and Burak Kesgin (eds.), Lost Kingdom: Animal Death in the Anthropocene (Wilmington, Delaware: Vernon Press, 2024), xxxiv + 343 pp., $ 62.00 (pbk), ISBN: 979-8-8819-0010-6.